A nonlinear theory for fibre-reinforced magneto-elastic rods. (17th January 2018) - Ciambella, Jacopo; Favata, Antonino; Tomassetti, Giuseppe
Abstract : We derive a model for the finite motion of a fibre-reinforced magneto-elastic rod. The reinforcing particles are assumed weakly and uniformly magnetized, rigid and firmly embedded into the elastomeric matrix. We deduce closed-form expressions of the quasi-static motion of the rod in terms of the external magnetic field and of the body forces. The dependences of the motion on the shape of the inclusions, their orientation, their anisotropic magnetic properties and the Young modulus of the matrix are analysed and discussed. Two case studies are presented, in which the rod is used as an actuator suspended in a cantilever configuration. This work can foster new applications in the field of soft-actuators.